Stability of visual acuity after cessation of occlusion therapy in patients of amblyopia - Nazir, Arjumand; Wani, Fayaz A.; Shah, Sumaya; Dar, Saleema (International Journal of Research in Medical Sciences, 2017)
Background: It is generally recognized that most children with amblyopia have an improvement of visual acuity (VA) with treatment, little is known about the course of vision once treatment is decreased or stopped in a child. The treatment of amblyopia in children is frequently discussed in the literature; however, there is a lack of research into which method of treatment cessation is the most appropriate once therapy has been completed. We undertook this specifically designed prospective study to directly compare the potential relationship between the method of therapy cessation and the short-term (12-weeks) recurrence of amblyopia. Methods: Fifty children of 5-14 years of age group with different types of amblyopia fulfilling the inclusion criteria were included in the study. Once BCVA was achieved, the subjects were randomized into one of two groups; abrupt cessation group or therapy tapering group. In subjects of tapered group occlusion was reduced from full-time occlusion to 50% of waking hours at BCVA and then additional by 50% at the 4-week’s study visit with occlusion being discontinued completely at the 8-week’s visit. All subjects in the abrupt cessation group stopped their full-time occlusion completely at the Best corrected visual acuity (BCVA). All subjects were followed for 3 consecutive 4-weeks intervals, for a total of 12 weeks, to assess the short-term recurrence rate of amblyopia. Results: The overall results show that at 12-weeks study outcome visit, 9 of the 50 subjects developed recurrence. Out of the total of 9 recurrences, 5 (20%) occurred in abrupt cessation group and 4 (16%) occurred in gradual cessation group. Comparing the time of occurrence of recurrence of amblyopia between the 2 studied groups, the recurrence of amblyopia was more during first 4 weeks of study 60% in abrupt group, whereas in gradual group all the recurrences occurred between 8 and 12 weeks visits. The pre-treatment VA and BCVA had a significant impact on the recurrence of amblyopia. Conclusions: In present study, the results demonstrate that the overall risk of amblyopia recurrence is 18% and the difference in the risk of amblyopia recurrence between the abrupt cessation group and the gradual cessation group (20% vs. 16%) is not statistically significant.